Treatment of Septicaemic Cutaneous Ulcerative Disease in an Indian Flap Shell Turtle: A Case Report - Sab, Jafar; Kumar, Niteesh; Golasangi, Sateesh Ashok; Kanteppa, Praveen Madugonda; Gangaram Bijurkar, Rajeshwar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Slowly but surely, turtles have become the pet of choice for many, rising to popularity in recent years. Septicaemic  Cutaneous Ulcerative Disease (SCUD) or Shell rot is a critical  issue in aquatic turtles and some reptiles caused by a bacterial  or fungal infection. This may occur due to lack of knowledge  of housing, i.e., keeping the turtles in dirty water or providing  mouldy bedding and some environmental factors like high  humidity and low temperatures are responsible for the  occurrence of this disease (Lingayat et al., 2022). If proper  measures for the control of shell rot are not taken, it can  cause rot through the bone and into the body cavity (Khan  et al., 2019). The Gram-negative bacteria that are normally  present in the environment are the most common cause of  bacterial infection (Kasim et al., 2017). Affected turtles show  clinical signs such as presence of white spots on shell and  hyperaemia in early stages of the disease, later cutaneous  ulceration and fibrin deposit on the shell can be seen (Fowler  and Miller, 2008; Jadhav et al., 2020). This documentation  describes the successful treatment of septicaemic cutaneous  ulcerative disease in an Indian flap shell turtle.
Keywords: turtles; rising; popularity; Septicaemic; Cutaneous; Ulcerative; Disease